The Provo International Conference on the Dead Sea Scrolls : technological innovations, new texts, and reformulated issues - Parry, Donald W.; Ulrich, Eugene, 1938- (Studies on the Texts of the Desert of Judah, 1999)
This volume contains the published proceedings of the conference on the Dead Sea Scrolls, held at Provo, Utah, July 15-17, 1996. Forty-three articles, all dealing with various aspects of the Scrolls, are placed under the following divisions: Technology, Editions and Analyses of Texts, The Qumran Community, Calendar, Levi and the Priesthood, Messianism and Eschatology, and Wisdom and Liturgy. The volume offers the most recent scholarship on a number of issues and topics pertaining to the Qumran community, newly translated biblical and non-biblical texts, and technological advances that assist scholars and researchers in accessing and studying the scrolls. The section that pertains to technology, for example, focuses on DNA techniques to analyze Scroll fragments and an imaging radar system that has archaeological applications to Qumran and its environs. Another section addresses the question of how and where the Qumranites lived and speaks concerning Qumran names.